Increased mouse double minute X expression in human placental villous macrophages (Hofbauer cells) in gestational diabetes mellitus - Arlıer, Sefa; Kükrer, Sadik; Adıgüzel, Cevdet (Journal of Surgery and Medicine, 2021)
Background/Aim: Gestational diabetes mellitus is a common metabolic problem in pregnancy, and its prevalence ranges between 5-20%. Hofbauer cells are tissue macrophages of the feto-placental component that are raised in the villous tree of the placenta during pregnancy, but their quantity falls off with growing gestational age. We theorize that Hofbauer cells play a significant role in placental pathophysiology in GDM by controlling the MDMX (mouse double minute X/MDM4/HDMX) gene. Methods: We performed immunohistochemistry on human placental specimens to determine cell-specific expression of MDMX in Hofbauer cells (HC) among the control and GDM (n=8 in each group) groups with matching gestational ages. Results: Immunohistochemical analysis revealed that MDMXs were secreted by Hofbauer cells in the placental villous tree and compared to the placenta got from normal pregnancies, significantly higher MDMX HSCORE levels were detected in placenta Hofbauer cells (32.8 (24.52) vs. 190.1 (32.54), P=0.001) of the GDM group. Conclusion: We revealed Hofbauer cells to be a source of MDMX secretion in human placenta. MDM2 levels in Hofbauer cells are also increased in GDM. This study found higher levels of MDMX in the Hofbauer cells from GDM placentas, suggesting an induction of MDMX secretion. GDM interaction in placental Hofbauer cells may contribute to GDM-associated feto-placental complications. Further studies are needed to define the significance of this relationship.